Ceftriaxone Degradation by Titanium Dioxide (TiO2) Nanoparticles: Toxicity and Degradation Mechanism - Mohammad Rofik Usman; Azmi Prasasti; Sovia Islamiah; Alfian Nur Firdaus; Ayu Wanda Marita; Syamsiyatul Fajriyah; Eka Fitri Yanti (Syarif Hidayatullah State Islamic University, 2020)
Ceftriaxone is a third generation of cephalosporin antibiotics that commonly used in patients with ulcers. Ceftriaxone residues in the environment are degraded using Titanium dioxide (TiO2) nanoparticles. Degradation of ceftriaxone using TiO2 nanoparticles was influenced by environmental conditions, such as light sources, pH of the solution, the mass of TiO2 nanoparticles, and the length of radiation. The remained ceftriaxone was analyzed by using a spectrophotometer UV-visible. The toxicity of the solution after the degradation process was tested on Escherichia coli and the type of products resulted was analyzed using Liquid Chromatography-Mass Spectrophotometry (LC-MS). The optimum conditions in degrading 50 mL 250 ppm ceftriaxone was radiation under a mercury UV lamp (white), pH 8, and 100 mg of TiO2 nanoparticles for 9 hours. The degradation degree of ceftriaxone obtained was 96.52%, producing simpler compounds that not toxic to E. Coli.